Upaya Guru dalam Meningkatkan Kemampuan Membaca Kitab Kuning Santri Tingkat Wustho Madrasah Diniyah - Hasyim; Mufidurrohman (CENDEKIA, 2021)
Success in reading the yellow book requires a teacher's strategy / efforts carried out by the asatidz / teacher council. This study has the aim of knowing the teacher's efforts in improving the ability to read the yellow book. This type of research is a qualitative research that collects data using interview and documentation methods. Based on the theory, the results of observations and interviews can be concluded 1. The teacher's efforts in improving the ability to read the yellow book are the teacher providing daily nahwu material, increasing class hours, using the sorogan method, giving mufrodat (vocabulary) doing questions and answers during madrasah, getting used to reading the mabadiul fiqhiyah book, accuracy in reading the yellow book, understanding in exploring the contents of the yellow book reading, and the ability to express the contents of the yellow book reading. 2. supporting factors and inhibiting the ability to read the yellow book. The teacher gives motivation to read often, uses an interesting learning process, and has low interest.